PENERAPAN SISTEM PENILAIAN KINERJA BERBASIS KOMPETENSI UNTUK PELAKU USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) - Riduan Siagian; Adrian K. Tarigan; Rudi Lingga (Jurnal Industri Kreatif dan Inovatif, 2025)
This Community Service Program (PKM) activity aims to help MSMEs implement a competency-based performance assessment system to ensure clearer division of labor, increased productivity, and more consistent service/product quality. Partners' issues include the lack of written work standards, subjective employee assessments, unclear targets, and difficulty in determining training needs. The program is implemented through needs assessments, the development of a simple MSME competency dictionary, the creation of assessment tools (competency forms and operational KPIs), assessment implementation training, and trial assistance for a specific period. The output is a performance assessment system package (competency + KPI) ready for use by MSMEs, complete with assessment SOPs, sample forms, and competency development plans.